A component analysis of awareness training for reducing speech disfluencies. Issue 2 (6th November 2020) - Montes, Christina C.; Heinicke, Megan R.; Guendulain, M. Alexander; Morales, Elizabeth
Abstract : Recent literature supports using an awareness training treatment package to decrease speech disfluencies for college students delivering short speeches. This package includes identifying speech disfluencies first via a video recording (video training), then during in vivo speech practice (in vivo training). However, the literature lacks an evaluation of these subcomponents, which poses a barrier to better understanding the efficiency, social validity, and potential underlying behavioral principles of awareness training. We conducted an add‐in component analysis with 8 college students by implementing either video or in vivo training first, evaluating treatment effects via a posttest, then implementing the remaining subcomponent, if warranted. We found that in vivo speech practice may be sufficient for reducing disfluencies for some participants, but a treatment package including the sequential application of both video and in vivo training is more likely to result in marked behavior change.